Designing Holistic Islamic Learning Design (HILD) for Islamic Religious Education in the Digital Era - Hanasto, Hanasto; Sukiman, Sukiman; Arifin, Zainal (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aimed to develop and evaluate the Holistic Islamic Learning Design (HILD) framework as an integrative instructional model for contemporary IRE. A Design-Based Research (DBR) methodology was employed through iterative phases of needs analysis, framework design, implementation, evaluation, and refinement at SMP Muhammadiyah Al Mujahidin Gunungkidul, Yogyakarta. Data were collected through classroom observations, semi-structured interviews, questionnaires, document analysis, and expert validation, and analyzed using thematic analysis, methodological triangulation, descriptive statistics, and iterative reflection. Quantitative expert validation demonstrated a high level of content validity, with an overall mean score of 4.80/5.00 (Excellent). Dimension-specific scores included pedagogical coherence (4.82), integration of Islamic values (4.91), content relevance (4.78), Islamic digital literacy components (4.76), and assessment design (4.73), all categorized as Excellent. Qualitative findings further revealed that HILD enhanced learner engagement, reflective learning, ethical digital awareness, contextual understanding of Islamic teachings, and character formation. The resulting framework integrates five complementary dimensions Spiritual Integration, Reflective Learning, Contextual Engagement, Islamic Digital Literacy, and Character Development into a coherent pedagogical model. This study contributes a theoretically grounded and empirically validated framework that advances holistic Islamic pedagogy and provides practical guidance for curriculum innovation and future implementation across diverse educational contexts.